Forming-ready resistance random access memory using randomly pre-grown conducting filaments via pre-forming. (May 2020) - Jeon, Dong Su; Park, Ju Hyun; Kang, Dae Yun; Dongale, Tukaram D.; Kim, Tae Geun
Abstract: The electrical forming is among the issues to be considered during practical applications of resistive switching random access memory (ReRAM) arrays. The typical electrical forming process increases the power budget and circuit complexity of the ReRAM arrays. From the material engineering point of view, most competitive ReRAM materials require higher forming voltages than the set voltages for efficient device operation. Considering these bottlenecks, herein, we report a novel method for a substantial reduction of the forming voltage to a range close to the set voltage. The proposed forming method covers cells in more than the 700 μm range, using a one-time pre-forming process. Randomly grown filaments completely formed over the active layers during pre-forming are reused for device operation without the need for further forming. To validate this method, we fabricated 8 × 8 ReRAM arrays with two conductive filament-based mechanisms namely valance change and electrochemical migration and each of the eight cells in line was set as the test sample to confirm the completion of the forming. All the eight cells in line had initial set voltages of 1 V, while the reference samples had forming voltages of 3 V. The results indicate that electrical forming had already occurred in the eight cells under the one-time bias application; thus, a range of cells spread over more than 700 μm was formed with the proposed method. This method is advantageous for the circuit design of ReRAM arrays with forming-free behavior.